The impact of platelets on pulmonary microcirculation throughout COVID-19 and its persistent activating factors - Xiang, Mengqi; Wu, Xiaoming; Jing, Haijiao; Liu, Langjiao; Wang, Chunxu; Wang, Yufeng; Novakovic, Valerie A.; Shi, Jialan (Frontiers in Immunology, 2022)
Patients with COVID-19 often have hypoxemia, impaired lung function, and abnormal imaging manifestations in acute and convalescent stages. Alveolar inflammation, pulmonary vasculitis, and thromboembolism synergistically damage the blood-air barrier, resulting in increased pulmonary permeability and gas exchange disorders. The incidence of low platelet counts correlates with disease severity. Platelets are also involved in the impairment of pulmonary microcirculation leading to abnormal lung function at different phases of COVID-19. Activated platelets lose the ability to protect the integrity of blood vessel walls, increasing the permeability of pulmonary microvasculature. High levels of platelet activation markers are observed in both mild and severe cases, short and long term. Therefore, the risk of thrombotic events may always be present. Vascular endothelial injury, immune cells, inflammatory mediators, and hypoxia participate in the high reactivity and aggregation of platelets in various ways. Microvesicles, phosphatidylserine (PS), platelets, and coagulation factors are closely related. The release of various cell-derived microvesicles can be detected in COVID-19 patients. In addition to providing a phospholipid surface for the synthesis of intrinsic factor Xase complex and prothrombinase complex, exposed PS also promotes the decryption of tissue factor (TF) which then promotes coagulant activity by complexing with factor VIIa to activate factor X. The treatment of COVID-19 hypercoagulability and thrombosis still focuses on early intervention. Antiplatelet therapy plays a role in relieving the disease, inhibiting the formation of the hypercoagulable state, reducing thrombotic events and mortality, and improving sequelae. PS can be another potential target for the inhibition of hypercoagulable states.